Comparison of next generation sequencing, droplet digital PCR, and quantitative real-time PCR for the earlier detection and quantification of HPV in HPV-positive oropharyngeal cancer. (May 2022) - Mattox, Austin K.; D'Souza, Gypsyamber; Khan, Zubair; Allen, Hailey; Henson, Stephanie; Seiwert, Tanguy Y.; Koch, Wayne; Pardoll, Drew M.; Fakhry, Carole
Highlights: HPV DNA is often detected by qualitative PCR, real time PCR, and other technologies including NGS and ddPCR are being explored. NGS and ddPCR in plasma and NGS in oral rinse have good sensitivity for HPV16-OPC. HPV levels detected in plasma by NGS may mirror the clinical course of HPV-positive head and neck cancer. Abstract: Background: Human papillomavirus (HPV) causes nearly 80% of oropharynx cancers diagnosed in the United States, with incidence increasing each year. Analysis of cfDNA in plasma and oral rinse has the potential to detect these cases earlier than their typical presentation, but their utility and the best method to detect HPV in plasma and oral rinse samples is unknown. Materials and Methods: We directly compared next generation sequencing (NGS), droplet digital PCR (ddPCR), and quantitative real-time PCR (qPCR) for their ability to detect HPV16 DNA in plasma and oral rinse from 66 patients diagnosed with HPV16-positive oropharyngeal cancer (HPV16-OPC). Results: HPV DNA detection by NGS and ddPCR in plasma samples both had good sensitivity (70%) for HPV16-OPC compared to 20.6% sensitivity by qPCR ( p  < 0.001). In oral rinse, NGS demonstrated a superior sensitivity of 75.0% as compared to both ddPCR (8.3%, p <  0.001) and qPCR (2.1%, p  < 0.001). In a limited cohort of follow up patients, HPV levels detected in plasma by NGS but not ddPCR or qPCR reflected disease remission or progression. Conclusions: These results suggest that NGS has the best sensitivity for detecting HPV in both plasma and oral rinse and may play a role in monitoring patients for disease recurrence. Additional studies are needed to define the specificity of NGS for similar patient cohorts.